CONSISTING OF ECOLOGICAL SAFETY OF OIL AND GAS EXTRACTIVE INDUSTRY - Шкіца, Л. Є.; Яцишин, Т. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The main factors that influence the state of ecological security in oil-and-gas mining sphere have been considered. Brief examination of research directions of the leading scientists in ecological security have been carried out. Some measures of preventing the appearance of new extraordinary situations in oil-and-gas mining sphere have been suggested.